Análise da secagem de pastas em leito de jorro - Almeida, André Ricardo Felkl de (2009)
The objective of this Doctoral Thesis was to analyse the fluidynamics and the heat and mass transfer of paste drying in a spouted bed under transient operation and to obtain detailed experimental data on the disturbed response of the system due to the presence of the liquid phase. This work also comprises the application of a CST model to predict temperature and moisture profiles in both the gas and solid phases. The paste-like matter employed in the experiments was distilled water, wastewater sludge, skim milk, homogenized whole egg and calcium carbonate. For each one of these pastes, experiments were done in two different spouted bed configurations (full and half column bed) operating with different feed rates, under inlet spout air flow rate at 15 and 30 % above the minimum spouting velocity and temperatures of 80 and 100 °C. In the full column spouted bed, measurements of inlet air flow rate variations, pressure drop, inlet air temperature, particle bed temperature at three axial positions in the annulus, outlet air temperature, dry and wet bulb temperatures at the cyclone exhaust and moisture content of powder and paste coat of inert particles were done. For the half column spouted bed, measurements of inlet air flow rate variations, pressure drop, inlet and outlet air temperature, dry and wet bulb temperatures at the cyclone exhaust, particles velocities in the annulus, spout and fountain, spout channel shape and dimensions and fountain high were done. The results obtained showed that the transient operation analysis was adequate and encouraging as a means to obtain further information on the drying process in spouted bed. Among the main results of this work is the important finding that the time required for the spouted bed to reach steady state may largely vary depending on the feed flow rate and spouting characteristics. The fluidynamics analysis showed that spouting characteristics may significantly change, indicating system instability, depending on the type of paste and the concentration and flow rate of the feed. As far as the CST model is concerned, it was seen that experimental data and predicted values were in good agreement, although the drying kinetic equation was highly dependent on paste concentration and density.